JĘZYKOWE ŚRODKI WARTOŚCIUJĄCE W WYROKACH FRANCUSKIEGO SĄDU KASACYJNEGO - Dolata-Zaród, Anna (Neofilolog, 2020)
This article attempts to describe the means of evaluation applied in French legal language. Analysing verdicts from the French court (Cour de cassation), this paper attempts to show ways to uncover the values system held by the judge. In order to achieve this aim, four groups of evaluative operators (modal truth-functional connectives, amplifying operators, emotive-evaluative modal operators and mental operators) are shown. The corpus under analysis is characterised by three aspects: intentional, conventional and institutional, as it makes references to the group of set convictions concerning the nature of a particular community. Thus one could see here a relation between the values behind the arguments in the verdict and the language used to express them.